ANALISIS PERSEPSI KEGUNAAN, PERSEPSI KEMUDAHAN, KESIAPAN TEKNOLOGI INFORMASI, KEAMANAN DAN KERAHASIAAN TERHADAP MINAT PERILAKU PENGGUNAAN E-FILLING - Santioso, Linda; Daryatno, Andreas Bambang; Aristha, Adya Juni (Akuntansi Krida Wacana, 2018)
The purpose of this research is to determine the effect of perceived usefulness, perceived ease of use, readiness of information technology, security and privacy of the tax payer’s interest to use the e-filling system. The research data covers primary data obtained through questionnaires. The subjects of this research is the taxpayer listed on KPP Pratama Jakarta-Cengkareng. Based on the test results R2 can be concluded that the variation of the variables (perceived usefulness, perceived ease of use, readiness of information technology, security and privacy) are able to explain by 29,2%, while the remaining 70,8% can be explained by other variables which are not included in this research model and the result showed that all independent variables have influence of the tax payer’s interest to use the e-filling system.Keywords: E-filling, Technology Acceptance Model, perceived usefulness, perceived ease of use, readiness of information technology, security and privacy